Polimorfisme Tawon Vespid (Hymenoptera; Vespidae) Asal Indonesia Dengan Morfologi Berbasis Cladistic: Polimorfisme tawon vespid (Hymenoptera: Vespidae) asal Indonesia dengan morfologi berbasis cladistic - Ramadhila, Yelsha; Nugroho, Hari; Jane, Erfanus; Ahmad, Intan (Perhimpunan Entomologi Indonesia, 2023)
Wasps in the family of Vespidae often have a yellowish black color with white or brown markings, but some species have variations in their markings and coloring. There is limited information available about the distribution of these marking patterns within the Vespidae Family. To clarify their taxonomic status, this study aims to examine the marking patterns of Vespid wasps that are widely distributed in the Indonesian Archipelago and to explore correlations with their biogeographical distribution patterns. In this study, specimens from three different locations (Bandung, Sumedang, and Purworejo) and specimens from the Museum Zoologicum Bogoriense (MZB) were examined. A total of 31 individuals from five different species were analyzed based on their morphological features. The data collected was coded and analyzed using cladistic methods, and the results were used to create cladogram trees for each of the five species i.e., Phimenes flavopictus, Polistes stigma, Apodynerus troglodytes, Vespa affinis, and Vespa velutina, showing their biogeographical distribution. The cladistic analysis in this study showed the relationships between the different species based on their morphological characteristics. The arrangements of the clades were determined using the Euclidean method in R studio. The results showed that P. flavopictus has two clades based on the marking patterns on their thorax and abdomen, while the other species i.e., Po. stigma, V. affinis, V. velutina, and A. troglodytes have three clades based on their coloring and marking patterns on all segments. The distribution of the Vespidae species appears to be scattered, with their patterns randomly distributed among locations.